When NGOs Fulfill State Obligations How NGO Laws in Africa Can Interfere with Social Rights of Beneficaries - Kahssay, Jihan (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2020)
Across parts of Africa, states have been restricting the operations, funding and speech of NGOs. Many have therefore expressed their concern that the cornerstones of a free civil society-the rights to free association and free speech-are under attack. However, another concern that warrants greater attention is whether such restrictive measures might also threaten the social rights of NGOs' beneficiaries. The ICESCR obliges states to take steps progressively towards the full realisation of social rights. How, then, should a state's social rights obligations be understood when NGOs enter the picture? How might those obligations affect a state's freedom to regulate NGOs? This book offers a systematic examination of the ways in which the social rights obligations of states towards beneficiaries can reorganise and refine our understanding of the regulatory relationship between states and NGOs. Einige afrikanische Staaten haben die Handlungsbefugnisse, Finanzierung und die Meinungsäußerung von NGOs eingeschränkt. Viele haben ihre Besorgnis darüber geäußert, dass die Eckpfeiler einer freien Zivilgesellschaft - das Recht auf Versammlungs- und Redefreiheit - angegriffen werden. Ein bislang eher weniger untersuchtes Problem ist jedoch, ob solche restriktiven Maßnahmen auch die sozialen Rechte der Begünstigten von NGOs gefährden könnten. Der UN-Sozialpakt verpflichtet die Staaten, Schritt für Schritt auf eine vollständige Verwirklichung der sozialen Rechte zuzugehen. Wie sollten also die Verpflichtungen eines Staates in Bezug auf soziale Rechte verstanden werden, wenn NGOs ins Spiel kommen? Wie könnten sich diese Verpflichtungen auf die Freiheit eines Staates auswirken, NGOs zu regulieren? Dieses Buch bietet eine systematische Untersuchung wie die sozialrechtlichen Verpflichtungen von Staaten gegenüber den Begünstigten unser Verständnis der Regulierungsbeziehungen zwischen Staaten und NGOs neu definieren und weiterentwickeln können.